Spleen Uptake on Bone Scan After Frequent Platelet and RBC Transfusions. (October 2016) - De Marini, Pierre; Laplace, Annegret; Matuszak, Julien; Fornecker, Luc-Matthieu; Namer, Izzie Jacques
Abstract : Abstract: A 21-year-old man, allogeneic hematopoietic stem cell transplantation recipient, was referred to our nuclear medicine department for a suspicion of knee osteonecrosis. Bone scan with 99m Tc-HMDP did not show abnormal bone uptake but an intense spleen accumulation. 18 F-FDG PET/CT performed on the same day showed no pathological spleen uptake. The patient had secondary hemochromatosis resulting from frequent transfusions in the setting of a chronic graft versus host disease with hemolysis and thrombocytopenia. The last RBC and platelet transfusions were performed 9 and 2 days before the examination, respectively. Secondary hemochromatosis and recent transfusions may explain our findings.